2017
DOI: 10.1161/jaha.117.007320
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation Promotion in a Rat Model of Rheumatoid Arthritis

Abstract: BackgroundThe prevalence of atrial fibrillation (AF) is significantly higher in rheumatoid arthritis (RA) patients, but the underlying mechanisms remain poorly understood. The goal of this study was to assess the effects of RA on AF susceptibility and atrial arrhythmogenic remodeling in a rat model of RA.Methods and ResultsCollagen‐induced arthritis was induced in rats by immunization with type II collagen in Freund's incomplete adjuvant. Among the rats that developed arthritis, AF susceptibility and atrial re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 35 publications
(46 reference statements)
1
19
0
Order By: Relevance
“…In addition, as already described (Fig. 3), histological analysis did not reveal increased LA fibrosis in the sham group, as would be expected in rats exposed to systemic inflammation 31,32 .…”
Section: Characterization Of Intrinsic Af Substrate In the Implanted supporting
confidence: 85%
See 1 more Smart Citation
“…In addition, as already described (Fig. 3), histological analysis did not reveal increased LA fibrosis in the sham group, as would be expected in rats exposed to systemic inflammation 31,32 .…”
Section: Characterization Of Intrinsic Af Substrate In the Implanted supporting
confidence: 85%
“…This intriguing finding led us to several additional experiments in order to try to reveal possible source\s for this phenomenon. The results strongly argue against the involvement of systemic inflammation as an underlying mechanism based on direct serum measurements of inflammatory cytokines as well as the absence of atrial fibrosis which is expected to occur in the presence of systemic inflammation 31,32,46 . Post-operative AF due to the thoracotomy we performed in the implantation surgery is another option that should be considered.…”
Section: Scientific Reports |mentioning
confidence: 83%
“…investigation [31]. The discrepancies may be explained by the onset, severity and duration of the different arthritic protocols used in the latter and current studies.…”
Section: Plos Onementioning
confidence: 67%
“…However, no changes in pulsed Doppler markers of diastolic function (E/A) were observed in CIA rats compared to controls. In contrast, one study showed impaired early diastolic filling velocity (E) in female CIA rats [31]. No other markers of diastolic function were assessed in the respective https://doi.org/10.1371/journal.pone.0230657.g005…”
Section: Discussionmentioning
confidence: 97%
“…In many clinical studies, the prevalence of AF is shown to be increased in RA patients (43). In a collagen-induced arthritis rat model, RA can cause AF and increase AF duration (44), suggesting roles in the initiation and maintenance of the arrhythmia (41).…”
Section: Evidence Of a Relationship Between Systemic Inflammation And Afmentioning
confidence: 99%